Analysis of communication styles underpinning clinical decision-making in cancer multidisciplinary team meetings - Soukup, Tayana; Lamb, Benjamin W.; Green, James S. A.; Sevdalis, Nick; Murtagh, Ged (Frontiers in Psychology, 2023)
Introduction. Multidisciplinary team (MDT) meetings are a gold standard in cancer care. While they are trying to maximize productivity on the back of the steadily increasing workload, growing cancer incidence, financial constraints, and staff shortages, concerns have been raised with regards to the quality of team output with one MDT member reporting that “Sometimes we discuss up to 70 patients. This is after a whole day of clinics, and we don't finish until gone 19.00. Would you want to be number 70?”. This study aimed to explore systematically some of the dynamics of group interaction and teamwork in the MDT meetings. Materials and methods. This was a prospective observational study that took place across three university hospitals in the UK. Three cancer teams participated. Thirty-six weekly-meetings were video recorded, encompassing 822 case-reviews. A cross-section of the recordings was transcribed using Jefferson notation system and analyzed using frequency counts (Quantitative) and some principles of Conversation Analysis (Qualitative). Results. We found that across teams, surgeons were the most frequent initiators and responders of interactional sequences speaking on average 47% of the time during case discussions. The Cancer Nurse Specialists and coordinators were the least frequent with the former speaking 4% of the time and the latter 1% of the time. We also found that meetings had high levels of interactivity with an initiator-responder ratio of 1:1.63, i.e., for every initiated sequence of interaction, the initiator received more than a single response. Lastly, we found that verbal dysfluencies (laughter, interruptions and incomplete sentences) were more common in the second half of meetings where a 45% increase in their frequency was observed. Discussion. Our findings highlight the importance of teamwork in planning MDT meetings, particularly in relation to (1) cognitive load/fatigue and decision-making, (2) the hierarchy of clinical expertise and (3) the increased integration of patient psychosocial information to MDT discussion and their perspectives. Utilizing a micro-level methodology, we highlight identifiable patterns of interaction of participants in MDT meetings and how those patterns can be used to inform the optimization of team-working.